حماية ضحايا جريمة التمييز وخطاب الكراهية - محمد ياسين قلاطي; صبري غراري (My University, 2021)
ABSTRACT: Hate speech and discrimination crimes are crimes that affect or prevent the enjoyment of fundamental human rights, such as discrimination, exclusion or expression directed at an individual or group of individuals on the basis of a combination of factors such as nationality, religion, language, sex or geographical affiliation. Attention to these crimes has increased since the post-Second World War period. The various treaties and conventions, as well as legislation, have sought to reduce such crimes and to protect their victims. These victims are often vulnerable groups in need of legal protection. This has been sought by various international, regional and national actors, through the establishment of legal frameworks and mechanisms to help prevent and eliminate such crimes and protect the victims of such crimes by ensuring their health, psychological and social well-being, and simplifying their access to justice, the establishment of service centres to support and care for them, as well as the prevention of discrimination and hate speech and the protection of victims of such crimes, have also sought national legislation to impose severe penalties on offenders for such crimes, owing to the seriousness of such crimes and their possible development into more serious crimes such as hate crimes, genocide and other crimes based on discrimination and hate speech. .................. ملخص: تعد جرائم التمييز وخطاب الكراهية من الجرائم التي تمس أو تمنع من التمتع بحقوق الإنسان الأساسية، وتتمثل في التفرقة أو الاستثناء أو التعبير الموجه نحو فرد أو مجموعة من الأفراد على أساس مجموعة من العوامل كالقومية أو الدين أو اللغة أو الجنس أو الإنتماء الجغرافي، وغيرها من الأسس، ولقد زاد الاهتمام بهذه الجرائم منذ فترة ما بعد الحرب العالمية الثانية. وسعت مختلف المعاهدات والإتفاقيات وكذا التشريعات للحد من هذه الجرائم، وحماية ضحاياها، كون هؤلاء الضحايا غالبا ما يكونون من الفئات المستضعفة المحتاجة للحماية القانونية، وهذا ما سعى إليه مختلف الفاعلين الدوليين والإقليميين والوطنيين لتحقيقه، عن طريق وضع أطر قانونية وآليات تساعد على الوقاية من هذه الجرائم والقضاء عليها من جهة، وحماية ضحايا هذه الجرائم من جهة أخرى، وهذا عن طريق التكفل بهم صحيا ونفسيا واجتماعيا، وتبسيط إجراءات لجوئهم الى القضاء، وإنشاء مراكز خدمية لدعمهم والتكفل بهم، بالإضافة الى الوقاية من التمييز وخطاب الكراهية وحماية ضحايا هذه الجرائم، سعت كذلك التشريعات الوطنية لتوقيع عقوبات شديدة على المجرمين في هذه الجرائم، وهذا راجع لخطورة هذه الجرائم وإمكانية تطورها الى جرائم أشد خطورة كجرائم الكراهية والإبادة الجماعية وغيرها من الجرائم التي أساسها التمييز والخطاب المحرض على الكراهية. .................... Résumé : Les crimes de discrimination et les discours haineux sont des crimes qui affectent ou empêchent la jouissance de la discrimination, de l’exclusion ou de l’expression des droits fondamentaux de la personne à l’égard d’une personne ou d’un groupe de personnes sur la base d’une combinaison de facteurs tels que la nationalité, la religion, la langue, le sexe ou l’appartenance géographique, et d’autres motifs, et l’attention portée à ces crimes a augmenté depuis la période d’après-guerre. Divers traités et conventions ainsi que la législation ont été élargis pour réduire ces crimes et la protection des victimes, car ces victimes sont souvent des groupes vulnérables qui ont besoin d’une protection juridique et c’est ce que divers Les acteurs régionaux et nationaux ont cherché à y parvenir, en établissant des cadres juridiques et des mécanismes pour aider à prévenir et à éliminer ces crimes d’une part et à protéger les victimes de ces crimes en leur fournissant un soutien sanitaire, psychologique et social. et la création de centres de services pour les soutenir et les soutenir, en plus de prévenir la discrimination et les discours de haine et de protéger les victimes de tels crimes, la législation nationale a également cherché à introduire des peines sévères pour ces infractions. Cela est dû à la gravité de ces crimes et à leur potentiel d’évolution vers des crimes plus graves tels que les crimes haineux, les génocides et autres crimes fondés sur la discrimination et les discours haineux.